2014
DOI: 10.2176/nmc.oa.2013-0147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inner Membrane Tearing in the Treatment of Adult Chronic Subdural Hematoma: A Comparative Study

Abstract: The postoperative results of chronic subdural hematoma (CSDH) procedures using catheterization and tearing of inner membrane (CTIM) technique have not previously been discussed in the literature. This article compares the effects of CTIM technique on brain re-expansion and re-accumulation with cases operated on with a burr-hole craniotomy and outer membrane incision (BCOMI) technique. The study involved operations on 144 patients (Group 1) using the CTIM technique and 108 patients (Group 2) using the BCOMI tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
1
24
2
Order By: Relevance
“…From the results of the current study and the two articles that discussed the opening of the inner membrane during a burr-hole evacuation of a CSDH [17,18], it can be proposed that this operative step was not a riskadding but, apparently, a recurrence-preventing one. A prospective randomized controlled study is recommended to establish this finding.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…From the results of the current study and the two articles that discussed the opening of the inner membrane during a burr-hole evacuation of a CSDH [17,18], it can be proposed that this operative step was not a riskadding but, apparently, a recurrence-preventing one. A prospective randomized controlled study is recommended to establish this finding.…”
Section: Discussionmentioning
confidence: 84%
“…Kayaci et al [18] in their retrospective study found that the recurrence rate was zero in the 144 patients who underwent incision of the inner membrane during the burr-hole evacuation of their CSDH, but they did not mention the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were thinking that this method for a bleeding in peritentorial localization can be applied. ma and damage, decompressive craniectomy may be the decision [3][4][5][6][7]. It may also be the decision in uncal or trans-tentorial herniation situations with a Glasgow Coma Score higher than 3, diffuse cerebral edema and midline shift on brain CT images, an intra-cerebral pressure of over 40 mmHg within the first 48 hours of trauma [3][4][5].…”
Section: Why Did Not I Choose Any Other Approach To Remove the Hematoma?mentioning
confidence: 99%
“…The relaxation of temporal base has resulted in the dispersion of the peritentorial blood. It has been reported in a very limited number of studies in the literature that removal or reduction of the pressure on the temporal base has resulted in a motion in the subarachnoid space, together with the increased intracranial pressure, and that the cerebrospinal fluid has washed the blood on the tentorial surface and led to its distribution [7,8]. The blood on the tentorium may have migrated downward after being collected around the free edges of tentorium in the medial side [8].…”
Section: Why Did Not I Choose Any Other Approach To Remove the Hematoma?mentioning
confidence: 99%